Impact of histone H4K16 acetylation on the meiotic recombination checkpoint in Saccharomyces cerevisiae - Cavero, Santiago (Microb Cell, 2016)
In meiotic cells, the pachytene checkpoint or meiotic recombination checkpoint is a surveillance mechanism that monitors critical processes, such as recombination and chromosome synapsis, which are essential for proper distribution of chromosomes to the meiotic progeny. Failures in these processes lead to the formation of aneuploid gametes. Meiotic recombination occurs in the context of chromatin; in fact, the histone methyltransferase Dot1 and the histone deacetylase Sir2 are known regulators of the pachytene checkpoint in Saccharomyces cerevisiae. We report here that Sas2-mediated acetylation of histone H4 at lysine 16 (H4K16ac), one of the Sir2 targets, modulates meiotic checkpoint activity in response to synaptonemal complex defects. We show that, like sir2, the H4-K16Q mutation, mimicking constitutive acetylation of H4K16, eliminates the delay in meiotic cell cycle progression imposed by the checkpoint in the synapsis-defective zip1 mutant. We also demonstrate that, like in dot1, zip1-induced phosphorylation of the Hop1 checkpoint adaptor at threonine 318 and the ensuing Mek1 activation are impaired in H4-K16 mutants. However, in contrast to sir2 and dot1, the H4-K16R and H4-K16Q mutations have only a minor effect in checkpoint activation and localization of the nucleolar Pch2 checkpoint factor in ndt80-prophase-arrested cells. We also provide evidence for a cross-talk between Dot1-dependent H3K79 methylation and H4K16ac and show that Sir2 excludes H4K16ac from the rDNA region on meiotic chromosomes. Our results reveal that proper levels of H4K16ac orchestrate this meiotic quality control mechanism and that Sir2 impinges on additional targets to fully activate the checkpoint.